2022
DOI: 10.3390/v14051097
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Two Wild Bird-Origin H3N8 Avian Influenza Viruses to Mammalian Hosts

Abstract: Wild birds play an important role in the emergence, evolution, and spread of zoonotic avian influenza viruses (AIVs). However, there are few studies on the cross-species transmission of the H3N8 AIV originating from wild birds. In this study, we investigated the transmissibility and pathogenicity of two H3N8 low pathogenic avian influenza viruses (LPAIVs) isolated from wild birds, GZA1 and XJ47, to mammals. The HA genes of both strains belonged to Eurasian isolates, while the other genes were derived from a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Liang et al. 32 reported direct contact transmission to one of three guinea pigs for one of the viruses tested, but no transmission was observed for the second virus tested. Zhang et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Liang et al. 32 reported direct contact transmission to one of three guinea pigs for one of the viruses tested, but no transmission was observed for the second virus tested. Zhang et al.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, two studies 31 , 32 tested the transmissibility of Eurasian avian H3N8 viruses (with gene compositions different from those of the novel reassortant H3N8 viruses) in guinea pigs and ferrets. Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The genome-wide analysis of JX 5-1 reveals that its internal genes have a diverse variety of origins and that many of them are clustered with AIVs in Asian nations near China during the course of genetic evolution. Two H3N8 influenza viruses with wild bird origins—XJ47 and GZ—were shown to have comparable internal gene source dynamics to JX5-1 in a different investigation [ 58 ]. It is speculated that the migration of wild birds among Asian countries caused this frequent gene exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The results of animal experiments showed low pathogenicity of JX5-1 in mice and inefficient replication of the virus in the lungs, indicating that the strain is not well adapted to mammals. In another study, both strains of wild bird-origin H3N8 avian influenza virus were able to replicate efficiently in mice and guinea pigs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Our previous study confirmed that H3N8 could induce adaptive mammalian mutations. 5 AIV transmission from birds to humans is usually sporadic and occurs in specific contexts, mostly from contact with infected poultry or contaminated environments. However, owing to the widespread prevalence of this virus, more sporadic cases are expected in the future.…”
mentioning
confidence: 99%